UPAYA HUKUM NOTARIS DALAM MENJALANKAN KEWAJIBAN INGKAR SEBAGAI BENTUK PERLINDUNGAN RAHASIA JABATAN - Candra, Nur Choirullah Adi; Hoesin, Siti Hajati (Universitas Labuhanbatu, 2025)
A notary has the position of a public official authorized to draw up authentic deeds required by society in legal acts. In carrying out this role, a notary has the obligation of refusal, namely the obligation to maintain professional secrecy by refusing to provide testimony or disclose information related to a deed or any statement obtained in the course of duty, including during summons or examination by investigators, prosecutors, or judges. This obligation of refusal functions as a legal safeguard for notaries to ensure that professional secrecy is preserved and not misused. The role of the Regional Notary Honorary Council is crucial in this mechanism, as it has the authority to approve or reject requests for summons or examinations of notaries by law enforcement officers. This research applies a doctrinal legal method by examining relevant statutory provisions, doctrines, and literature. The findings show that the obligation of refusal is a legal instrument designed to protect the confidentiality of authentic deeds, while the Regional Notary Honorary Council, through its authority, acts as a filter to protect notaries from being compelled to disclose professional secrets without lawful grounds. Therefore, the obligation of refusal not only safeguards the interests of notaries but also upholds the principle of deed confidentiality to ensure legal certainty and protection for the parties involved. Keywords: Notary, Obligation of Refusal, Protection of Professional Secrecy, Regional Notary Honorary Council